P-732 Definitions and diagnostic criteria for unexplained infertility (UI) – a systematic review. (30th June 2022) - Raperport, C; Qureshi, D; Desai, J; Bhide, P
Abstract: Study question: What are the various inclusion criteria for the definition of unexplained infertility used for recruitment to clinical trials, and is there homogeneity of these definitions? Summary answer: There is a need to standardise the definition of unexplained infertility when recruiting for clinical trials to optimise interpretation of results and allow appropriate meta-analysis. What is known already: Unexplained infertility (UI) is a diagnosis of exclusion. The pathology underlying this diagnosis is likely to include different subtle contributing factors. Unfortunately there is no universally accepted definition of unexplained infertility. NICE in the UK, and ACOG/ASRM both have lists of recommended investigations but no specific minimum standards to define UI. Even the ICMART definition is ambiguous, describing 'apparently normal' ovarian function and ejaculate. This may lead to heterogeneity between inclusion criteria in relevant research studies. This introduces selection bias and renders meta-analysis of trial results less meaningful. A single definition would improve the quality of research for this important diagnosis. Study design, size, duration: A systematic review of primary research investigating definitions of unexplained infertility in humans. A thorough search of online databases Medline and Embase was performed from inception to November 2021. A bespoke Excel spreadsheet was used to collect data for baseline study characteristics and outcome data. Results are reported as percentages. Participants/materials, setting, methods: The search strategy included all primary research on heterosexual couple unexplained infertility in human participants. Papers with specified inclusion criteria were included and no date or language restrictions were applied. From 663 results, title and abstract screening identified 83 duplicates and 6 studies unsuitable for the review. A further 275 papers were excluded after full-text screening. 241 papers remained and their inclusion criteria recorded and analysed. Main results and the role of chance: Only 35.7% of papers specified duration of infertility. Timescales varied from 1 year (46.5%), 2 years (39.5%) or 3 years (14%). 85% papers specified that semen analysis should be 'normal'. Of these, 40% used the most recent WHO criteria. No other national or international criteria for grading semen analysis was identified. 90% studies required fallopian tube patency as an inclusion criteria. Of these, 65.4% specified bilateral patency. Methods for demonstrating patency included hysterosalpingogram (HSG) (15.7%), laparoscopy (18.4%), a combination of either (29.5%) or both (24.4%) of these or hystero-contrast-salpingography (0.9%). 11.5% papers did not specify an imaging modality. 48.5% included studies mentioned uterine cavity assessment, 65% of these using HSG to assess the cavity, other methods mentioned include ultrasound (26.5%) or hysteroscopy (15.4%). Only 5.4% papers required either exclusion of or evidence of only minimal endometriosis 80.5% of included papers required evidence of regular ovulation. 58.7% used luteal serum progesterone levels, 41.2% required regular cycles (patient-reported) and 17.5% used basal body temperature pattern assessment. Other methods mentioned by a minority of papers include endometrial biopsy, ultrasound follicular tracking, serum and urinary luteinising hormone levels. 44% studies required normal endocrine profiles of which 66% measured prolactin and FSH and 50% measured thyroid function. Limitations, reasons for caution: The strength of this study is that we included all primary research papers studying unexplained infertility with no time limitations. Included studies originated from across the world. This is a thorough representation of criteria used across all clinical trials for unexplained infertility. Wider implications of the findings: Only 63/241 (26%) studies included duration of infertility, tubal patency, proof of ovulation and semen analysis in their inclusion criteria. This demonstrates the need for standardisation of the definition of unexplained infertility. If future research can apply the same inclusion criteria this will reduce selection bias and allow appropriate meta-analysis. Trial registration number: NA